2011
DOI: 10.1162/jocn.2010.21549
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation between the Hippocampus and the Striatum during Episodic Encoding

Abstract: The hippocampus and the striatum are thought to play distinct roles in learning and memory, each supporting an independent memory system. A fundamental question is whether, and how, these systems interact to jointly contribute to learning and memory. In particular, it remains unknown whether the striatum contributes selectively to implicit, habitual learning, or whether the striatum may also contribute to long-term episodic memory. Here, we show with functional magnetic resonance imaging (fMRI) that the hippoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(65 citation statements)
references
References 76 publications
6
57
2
Order By: Relevance
“…Interpreting our findings based on the model of competition between these regions (Lee et al, 2008;Poldrack et al, 2001) suggests that in CD, increased potential to use striatum-based strategies for learning may inhibit activity within MTL, although an independent dysfunction of MTL cannot be excluded. Conversely, interpreting our findings based on a model of cooperation between these brain regions (Sadeh et al, 2011;Voermans et al, 2004) would suggest that in CD, inefficient representations of MTL-based strategies for learning may produce a compensatory modulation of striatal activity in the service of maintaining normal behavioral performance on the task, particularly when the task is difficult (as it was in our control condition). Cortical activations also differed across groups.…”
Section: Searching the Maze For Navigational Cuesmentioning
confidence: 72%
“…Interpreting our findings based on the model of competition between these regions (Lee et al, 2008;Poldrack et al, 2001) suggests that in CD, increased potential to use striatum-based strategies for learning may inhibit activity within MTL, although an independent dysfunction of MTL cannot be excluded. Conversely, interpreting our findings based on a model of cooperation between these brain regions (Sadeh et al, 2011;Voermans et al, 2004) would suggest that in CD, inefficient representations of MTL-based strategies for learning may produce a compensatory modulation of striatal activity in the service of maintaining normal behavioral performance on the task, particularly when the task is difficult (as it was in our control condition). Cortical activations also differed across groups.…”
Section: Searching the Maze For Navigational Cuesmentioning
confidence: 72%
“…Previous studies showed that several striatal subregions (especially caudate) and the hippocampus interact during episodic memory (41)(42)(43)(44)(45)(46), and considerable overlap has been observed in the pattern of functional connectivity for hippocampal and caudate seeds (47). This suggests that these regions are part of a shared functional network.…”
Section: Discussionmentioning
confidence: 94%
“…Two recent studies found increased correlation between the activity of the dopaminergic system and the hippocampus during successful encoding that required integration of information. The first study (Shohamy and Wagner, 2008) showed an increased correlation between activity in the hippocampus and the dopaminergic midbrain during successful versus unsuccessful generalization of associations, and the second study (Sadeh et al, 2011) found an increased correlation between the putamen and the hippocampus during successful episodic encoding. Although these studies did not report such correlations in the caudate nucleus, as part of the dopaminergic system, it is strongly connected to both the dopaminergic midbrain and the putamen.…”
Section: Discussionmentioning
confidence: 99%